Vakalarla Kalp Damar Cerrahisi II - Uyar, Sami; Hanedan, Bedia Mine; Durmaz, Hüseyin; Çelik, Ersin; Erkan, Muhammet Hüseyin; Usta, Sefer; Demir, İbrahim and Beyaz, Metin Onur and Umaroğlu Öztürk, Sevi and Kurtoğlu, Murat and Acır, İbrahim and Atay, Mehmet and Yeşiltaş, Mehmet Ali and Gökkurt, Yaşar and Hemşinli, Doğuş and Tunçay, Aydın and Topçu, Fatma Sena and Durmaz, Hüseyin and Müdüroğlu, Ayhan and Savran, Muhammed and Şimşek, Harun Aybars and Ömeroğlu, Suat Nail and Özdemir Şahan, Yasemin and Ayık, Mehmet Fatih and Canikoğlu, Mustafa and Barış, Özgür and Durmaz, Ayşegül and Telli, Alpaslan and Soydaş, Ömer Faruk and Arapi, Berk and Kocaoğlu, Alper Selim and Aslan Yağlı, Zeynep and Demirtaş, Mücahit and Yiğit, Fatih and Ergenç, Ebsar and Keleş, Ercan and Dönmez, Barış and Özocak, Okan and Güner, Yeşim and Eroğlu, Murat and Parlar, Ali İhsan and Kan, İrem İris and Yenigün, A. Orhun and Tel Üstünışık, Çiğdem and Özmen, Rifat and Sarı, Gülden and Durmaz, Ayşegül and Canikoğlu, Mustafa and Arıkan, Ali Ahmet and Onuk, Burak Emre and Selçuk, İsmail and Yılmaz, İrem and Mirizada, Miri and Aydoğmuş, İrem and Önder Kılıç, Ali and Sarıoğlu, Anıl and Kaya, Ahmet Deniz and Uyar, İbrahim and Apaydın, Koray and Erkul, Sinan and Gökçimen, Mecit and Dikkaş, Uğur and Ömeroğlu, Suat Nail and Çidem, Savaş (Academician Publishing Book DOI Portal, 2023)
-